2017
DOI: 10.1021/acs.orglett.7b01869
|View full text |Cite
|
Sign up to set email alerts
|

Columbamides D and E: Chlorinated Fatty Acid Amides from the Marine Cyanobacterium Moorea bouillonii Collected in Malaysia

Abstract: Two new chlorinated fatty acid amides, columbamides D (1) and E (2), along with apratoxins A and C and wewakazole, were isolated from the organic extract of a Moorea bouillonii sample from Sabah, Malaysia. Structure elucidation was accomplished by a combination of MS and NMR analyses. The total synthesis of all four stereoisomers of 1 was completed, and the absolute configuration was determined by chiral-phase HPLC and Marfey's analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…In other words, Apratoxin A has been frequently observed from Moorea bouilonii samples. The previous research of Moorea bouilonii in Mantanani Island confirms the presence of Apratoxin A, Apratoxin C, Wewakazole, and Columbamide, specifically Columbamide D and Columbamide E (Lopez et al, 2017). In the present study, these compounds were also observed, except for Columbamide E. This finding reveals how different environments may affect the secondary metabolites of the organisms.…”
Section: Identified Compoundssupporting
confidence: 89%
See 2 more Smart Citations
“…In other words, Apratoxin A has been frequently observed from Moorea bouilonii samples. The previous research of Moorea bouilonii in Mantanani Island confirms the presence of Apratoxin A, Apratoxin C, Wewakazole, and Columbamide, specifically Columbamide D and Columbamide E (Lopez et al, 2017). In the present study, these compounds were also observed, except for Columbamide E. This finding reveals how different environments may affect the secondary metabolites of the organisms.…”
Section: Identified Compoundssupporting
confidence: 89%
“…collected from Udar Island is rich in secondary metabolites, which are mainly peptides. The observed mass of Apratoxin A from the sample was similar to the Moorea bouilonii samples collected from Guam, Palau, Papua New Guinea, and Malaysia (Lopez et al, 2017;Matthew et al, 2010;Tan et al, 2013). In other words, Apratoxin A has been frequently observed from Moorea bouilonii samples.…”
Section: Identified Compoundssupporting
confidence: 73%
See 1 more Smart Citation
“…Two chlorinated fatty acid amide derivatives, columbamides D 263 and E 264, were isolated from Moorea bouilloni, collected near Mantanani Island, Sabah, Malaysia. 139 Total synthesis of all four stereosiomers of 263 enabled its absolute conguration to be assigned. 139 The remaining rst total syntheses were for 2,2 0 ,5,5 0 -tetrabromo-3,3 0 -bi-1H-indole, 140 biselyngbyaside, 141 and wewakazole B.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…139 Total synthesis of all four stereosiomers of 263 enabled its absolute conguration to be assigned. 139 The remaining rst total syntheses were for 2,2 0 ,5,5 0 -tetrabromo-3,3 0 -bi-1H-indole, 140 biselyngbyaside, 141 and wewakazole B. 142,143 Only one structure revision was reported for this phylum in 2017.…”
Section: Cyanobacteriamentioning
confidence: 99%